Linguistic underrepresentation in medical publishing: perspectives around the COVID-19 pandemic - Gonzalez-Rayas, Jose Manuel; Mendoza-Sigala, Marcela (Archives of Evidence-Based Medicine, 2023)
COVID-19 and the “new normal” have come here to stay. What initially emerged as a local outbreak transitioned into a global pandemic, and has caused more than 6 million deaths.2 The sudden onset of the SARS-CoV-2 crisis challenged health care systems in terms of both patient overflow and information paucity. As the new infectious agent was previously unknown, evidence was scarce and highly controversial. Nonetheless, after the novel coronavirus continued spreading, medical literature became available to the point that more than 72,000 articles were published in PubMed in 2020 (Figure 1). This number is around 80 times greater than the previous year.